Evaluation of thermal ageing activation energy of δ-ferrite in an austenitic stainless steel weld using nanopillar compression test. (September 2020) - Kong, Byeong Seo; Shin, Jiho; Obulan Subramanian, Gokul; Chen, Junjie; Jang, Changheui; Na, Ye-eun; Jang, Dongchan; Lee, Ho Jung; Yang, Jun-Seog
Abstract: Nanopillar compression tests were applied on δ-ferrites in austenitic stainless steel welds to measure the thermal ageing activation energy caused by spinodal decomposition. Welds of an austenitic stainless steel were thermally aged at 343, 375, and 400 o C for up to 20, 000 h. To avoid the interference of surrounding austenite matrix on embrittlement measurement, austenite matrix was selectively dissolved before the nanopillar fabrication. Using the yield stress changes measured by nanopillar compression tests, the thermal ageing activation energy of δ-ferrite was estimated as 154 KJ/mol, which was compared with literature results and the reasons of discrepancy were discussed. Graphical highlights: (a) SEM micrographs of δ-ferrite network after selective dissolution of austenite matrix, (b) fabrication of nanopillar from δ-ferrite, (c) the deformed nanopillar after compression test for 316 L weld aged at 400 o C for 20, 000 h, (d) the critical resolved shear stress (CRSS) vs. ageing time at different temperatures where non-linear fit and corresponding characteristic time constant are indicated, and (e) the activation energy of thermal ageing of δ-ferrite calculated from nanopillar compression tests. Image, graphical abstract